Chatib Sulaiman: Patriotic Fighter from Nagari Sumpur, West Sumatra - Fatimah, Siti; Lionar, Uun (Paramita: Historical Studies Journal, 2022)
This paper belongs to historical research or biographical research of a figure. In contrast to biographical research that has been done by other historians and researchers which generally emphasized on the history and role of a figure, this paper looks at the existence of a figure, named Chatib Sulaiman, from the geospatial setting of his birthplace, Sumpur, located on the lakeside of Lake Singkarak, West Sumatra. Chatib Sulaiman is quite different from other local figures in Minangkabau. This study aims at analyzing the process of character building of Chatib Sulaiman that is influenced by the spatial conditions of his birthplace in relation to the dynamics of his life and struggles. The results indicate that the existence of Chatib Sulaiman cannot be separated from the geospatial of Nagari Sumpur, his birthplace, which then has a very significant influence on the building of his character as a fighter. The existence of Nagari Sumpur with an egalitarian and democratic style has built the character of Chatib Sulaiman as an independent and open-minded person. Through the western education he has received, Chatib Sulaiman became a smart and skilled young man. He was at the forefront of opposing the practice of colonialism in West Sumatra. In his struggle, Chatib Sulaiman once led the Regional People's Defense Council, served as the secretary of the National Defense Front, and was the most prominent young man in West Sumatra when the physical revolution took place, especially during the PDRI (Emergency Government of the Republic of Indonesia) period.Tulisan ini termasuk penelitian sejarah atau penelitian biografis seorang tokoh. Berbeda dengan penelitian biografi yang telah dilakukan oleh para sejarawan dan peneliti lain yang pada umumnya menekankan pada sejarah dan peran seorang tokoh, tulisan ini melihat keberadaan seorang tokoh bernama Chatib Sulaiman, dari setting geospasial tempat kelahirannya, Sumpur, terletak di tepi danau Danau Singkarak, Sumatera Barat. Chatib Sulaiman cukup berbeda dengan tokoh-tokoh lokal lainnya di Minangkabau. Penelitian ini bertujuan untuk menganalisis proses pembentukan karakter Chatib Sulaiman yang dipengaruhi oleh kondisi spasial tempat kelahirannya dalam kaitannya dengan dinamika kehidupan dan perjuangannya. Hasil penelitian menunjukkan bahwa keberadaan Chatib Sulaiman tidak lepas dari geospasial Nagari Sumpur, tempat kelahirannya, yang kemudian berpengaruh sangat signifikan terhadap pembentukan karakternya sebagai seorang pejuang. Keberadaan Nagari Sumpur dengan gaya egaliter dan demokratis telah membangun karakter Chatib Sulaiman sebagai pribadi yang mandiri dan berpikiran terbuka. Melalui pendidikan barat yang diterimanya, Chatib Sulaiman menjadi pemuda yang cerdas dan terampil. Ia berada di garda terdepan menentang praktik kolonialisme di Sumatera Barat. Dalam perjuangannya, Chatib Sulaiman pernah memimpin Dewan Pertahanan Rakyat Daerah, menjabat sebagai sekretaris Front Pertahanan Negara, dan merupakan pemuda paling terkemuka di Sumatera Barat ketika terjadi revolusi fisik, terutama pada masa PDRI (Pemerintahan Darurat Republik Indonesia). Republik Indonesia) periode.Cite this article: Fatimah, S., Lionar, U. (2022). Chatib Sulaiman: Patriotic Fighter from Nagari Sumpur, West Sumatra. Paramita: Historical Studies Journal, 32(1), 11-22. http://dx.doi.org/10.15294/paramita.v32i1.31579